Fancy Nancy : fanciest doll in the universe - O'Connor, Jane.; Preiss-Glasser, Robin (New York, NY : Harper, 2013)
Fancy Nancy's sister, Jojo, has done something really bad and Nancy is livid. Jojo drew a tattoo on Nancy's precious doll. When Mom suggests a fancy doll party to make Nancy feel better, Nancy is excited to accept, but what if the doll drama is not over?
3.6
K-3
Text mainly in English with some French.
Keywords: Fancy Nancy (Fictitious character) -- Juvenile fiction; Dolls -- Juvenile fiction; Parties -- Juvenile fiction; Sisters -- Juvenile fiction; Fancy Nancy (Fictitious character) -- Fiction; Dolls -- Fiction; Parties -- Fiction; Sisters -- Fiction; Fancy Nancy (Fictional character) -- Fiction; Dolls -- Fiction; Parties -- Fiction; Sisters -- Fiction; Parties -- Fiction; Sisters -- Fiction; Dolls -- Fiction; Picture books for children